(untitled) (Proceedings of Southern Federal University. Philology, 2020)
It is argued that the skill of the writer is the ability to use the stereotypical views of readers as a basis for recognition and acceptance of the characters’ images. At the same time, individualization is layered on the stereotype, and is formed to a large extent due to the appeal to the combinative potential of the various comparisons, which embody the stereotype. The use of age stereotypes in the novel prose of M. A. Sholokhov is considered. It is noted that the writer resorts to stable comparisons with the lexical variation and expansion, appeals to individual comparisons, based on conjunctions and semantically connected with the preconceptions about age (individual ones are almost three times more than stable ones). The deployment of comparisons due to the spread of each full-valued component is also repetitive. More often than comparisons, based on conjunctions, the author uses comparative adverbs, which help him to focus the reader’s attention on the nuances of age characteristics. At the same time, the predominance of prefix-suffix derivatives (по-детски, по-молодому, etc.) over suffix derivatives (детски, старчески, etc.) allows us to conclude that Sholokhov tends to accentuate the detail as such but not the quality of it. If the comparisons, based on conjunctions, make it possible to emphasize a frequent deviation in the characteristic or in the behavior of the individual from the so-called standard, the adverbial comparisons are not so homogeneous: a third part of them allows to see the correspondence of personal characteristics expected for the particular age group. Keywords: Sholokhov, artistic detail, age, stereotype, comparison based on conjunction, comparative adverb, syntagmatics. DOI 10.18522/1995-0640-2020-1-27-35